Macroscopic and Microscopic Analysis of Development Mature Fruit Bruguiera gymnorrhiza (L.) Lamk - Handayani, S.; Setyoyuwono, S.; Aulani’am, Aulani’am; Suprayitno, E. (Proceeding International Conference on Global Resource Conservation, 2013)
The development of mature fruit Bruguiera gymnorrhiza (large mangrove leaf) are green color change (age 70 Daf), green-purple (age 80 Daf) and ended up being a full purple (90 Daf). Fruit is also experiencing accretion diameter, except for the tip (tip:1,14 to 1,13 cm; middle: 1,63 to 1,69 cm; base: 1,23 to 1,25 cm), lengthy (16,51 to 18,81 cm) and reduction weight (30,08 to 27,14). Increasingly fruit age, the harder texture (173,50 to 191,50 N). it was distinctive fruit flavors and slightly bitter tannins, so the fruit can not be consumed directly. The fruit (tip, middle and base) that have cell development is endocarp and mesocarp. Cells in the endocarp shape are a hexagon (tetrahedron) irregular, in Mesocarp cells undergo renewal and there is also a prism shape. It is evenly distributed throughout the cell wall thickening section (lacunnar). Types include parenchyma and collenchyma tissue. At the same eksocarp, endocarp cell shape, with tight cell structure, composed of epidermal cells and hypodermic. Cells of the epidermis have stomata.Keywords: B. gymnorrhiza, macroscopic, mature fruit, microscopicÂ